The Concept of a Distributed Repository for Validating X.509 Attribute Certificates in a Privilege Management Infrastructure. (2016) - Gergely, Adam Mihai; Crainicu, Bogdan
Abstract: The present paper proposes a conceptual method for implementing a distributed repository for X.509 Attribute Certificates in a Privilege Management Infrastructure. It describes the idea behind this kind of repository, the security advantages of having a distributed repository, problems and access methods, and finally the techniques used to store and access the attribute certificates for validation by the requesting clients.